The relationship between government expenditure and economic growth: An application on Turkish republics in transition process [Kamu harcamaları ve ekonomik büyüme İlişkisi: Geçiş sürecindeki Türk cumhuriyetleri Üzerine bir uygulama] - Esen Ö.; Bayrak, M. (Ahmet Yesevi University, 2015)
In this study the effects of public expenditures on economic growth for 5 Turkish Republics (Azerbaijan, Kazakhstan, Kyrgyzstan, Uzbekistan and Turkmenistan) in transition process are researched by using panel data analysis for the years 1990-2012. In this context, by using the panel unit root, panel cointegration and panel causality tests related with panel data analysis, long-term co-efficents between public expenditures and economic growth are studied. According to the analysis results, the presence of a positive and statistically significant relationship between public expenditures and economic growth is revealed in the long run. Within this context, the rise of public expenditures in the studied period revealed to be affecting economic growth in a positive manner. © 2015, Ahmet Yesevi University. All rights reserved.
Keywords: Economic growth; Panel data analysis; Public expenditures; Transition economies; Turkic republics